Monitoring the seasonal changes of an englacial conduit network using repeated ground-penetrating radar measurements - Church, Gregory James; id_orcid:0 000-0003-0114-9950; Grab, Melchior; id_orcid:0 000-0002-8293-4872; Schmelzbach, Cédric; id_orcid:0 000-0003-1380-8714; Bauder, Andreas; id_orcid:0 000-0001-7197-7706; Maurer, Hansruedi (Copernicus, 2020)
Englacial conduits act as water pathways to feed surface meltwater into the subglacial drainage system. A change of meltwater into the subglacial drainage system can alter the glacier's dynamics. Between 2012 and 2019, repeated 25 MHz ground-penetrating radar (GPR) surveys were carried out over an active englacial conduit network within the ablation area of the temperate Rhonegletscher, Switzerland. In 2012, 2016, and 2017 GPR measurements were carried out only once a year, and an englacial conduit was detected in 2017. In 2018 and 2019 the repetition survey rate was increased to monitor seasonal variations in the detected englacial conduit. The resulting GPR data were processed using an impedance inversion workflow to compute GPR reflection coefficients and layer impedances, which are indicative of the conduit's infill material. The spatial and temporal evolution of the reflection coefficients also provided insights into the morphology of the Rhonegletscher's englacial conduit network. During the summer melt seasons, we observed an active, water-filled, sediment-transporting englacial conduit network that yielded large negative GPR reflection coefficients (<−0.2). The GPR surveys conducted during the summer provided evidence that the englacial conduit was 15–20 m±6 m wide, ∼0.4m±0.35m thick, ∼250m±6m long with a shallow inclination (2∘), and having a sinusoidal shape from the GPR data. We speculate that extensional hydraulic fracturing is responsible for the formation of the conduit as a result of the conduit network geometry observed and from borehole observations. Synthetic GPR waveform modelling using a thin water-filled conduit showed that a conduit thickness larger than 0.4 m (0.3× minimum wavelength) thick can be correctly identified using 25 MHz GPR data. During the winter periods, the englacial conduit no longer transports water and either physically closed or became very thin (<0.1 m), thereby producing small negative reflection coefficients that are caused by either sediments lying within the ...